2022
DOI: 10.35445/alishlah.v14i2.1611
|View full text |Cite
|
Sign up to set email alerts
|

Redesign of Indonesian Language Textbooks Based on Student Needs Analysis

Abstract: The available Indonesian language textbooks, both compulsory and commercial, might not fully meet the students' future needs and industrial demands. This study examines the concept of redesigning Indonesian language textbooks based on students' needs analysis, presenting a critical review of several relevant studies from journals, conference articles, and other permanent references. This study reveals three primary results. First, teachers are responsible for evaluating the textbooks' content and determining h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In its use, the facts show that there are numerous issues about textbooks in the classroom. Previous researches have shown that existing English textbooks do not meet the criteria for good textbooks and do not focus on needs analysis (Nesi, Su, & Pristiwati, 2022). Other previous research findings demonstrate that English textbooks only meet the design and layout criteria (Rahma, Ampa, & Nappu, 2021;Said, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In its use, the facts show that there are numerous issues about textbooks in the classroom. Previous researches have shown that existing English textbooks do not meet the criteria for good textbooks and do not focus on needs analysis (Nesi, Su, & Pristiwati, 2022). Other previous research findings demonstrate that English textbooks only meet the design and layout criteria (Rahma, Ampa, & Nappu, 2021;Said, 2018).…”
Section: Introductionmentioning
confidence: 99%